Characterization of Gardenia tea based on aroma profiles using GC-E-Nose, GC-O-MS and GC × GC-TOFMS combined with chemometrics - Jialing Xie; Qiwei Wang; Hongchun Cui; Lilei Wang; Yuliang Deng; Haibo Yuan; Jiayi Zhu; Yanqin Yang; Yongwen Jiang (Beverage Plant Research)
Gardenia tea (GET) is one of the typical representatives of Chinese scented tea and is loved by consumers for its pleasant aroma. In the present study, the volatile profiles of GET were characterized by gas chromatography electronic nose (GC-E-Nose), comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry (GC × GC-TOFMS) and gas chromatography-olfactory-mass spectrometry (GC-O-MS) combined with chemometrics. Satisfactory discrimination was obtained by GC-E-Nose combined with principal component analysis, with the cumulative contribution rate reaching 86.74%. A total of 202 volatile compounds were identified in GET by GC × GC-TOFMS, among which esters, alkenes and alcohols were the dominant volatile components. Moreover, 24 key odorants were screened out from GET based on odor activity value ≥ 1 and GC-O-MS results. The aroma wheel of GET with six attributes of 'fruity', 'green', 'floral', 'other', 'woody', and 'roasted' was constructed to visualize the contributions of those key volatile compounds. The results provide a new strategy to elucidate the volatile profiles and aroma wheel of scented tea.